Phosphorus (P) improves industrial tomato quality and yield in soil with high phosphorus content - Filho, Arthur Bernardes Cecílio [UNESP]; Trevizaneli, Bruno; Rugeles-Reyes, Sergio Manuel (Southern Cross Publishing, 2020)
Soils under intensive and successive cropping with central pivot irrigation tend to present high nutrient contents, especially phosphorus (P), which is a nutrient with a great impact on the yield and quality of agricultural products. Among the rotating crops, the application of high P rates is common in processing tomato, although not supported by research. This work evaluates the effect of phosphate fertilization (0, 200, 400, 600, 800, and 1000 kg ha-1 P2O5) on the yield and quality of industrial tomato 'Heinz 9553' grown in a soil with high available P content (145 mg dm-3) resulting of an intensive vegetables cultivation, which have high demand by P. The highest total (127.4 t ha-1) and commercial (108.6 t ha-1) yields were obtained with 413.9 and 384 kg ha-1 P2O5, respectively. The results showed that pH of tomato juice, the percentages of green, red, and commercial fruits were not influenced by the applied P rates. However, nutrient delivery increased the soluble solids content up to 356 kg ha-1 P2O5, which is interesting for tomato processing. After harvesting the fruits, the available soil P content was increased with P supply to the plants. For improvement of commercial yield and soluble solids characteristics, the tomato crop shall be fertilised with P even though the soil has high P content.
Keywords: Agribusiness; Commercial fruits; Phosphate fertilization; Solanum lycopersicum; Soluble solids